Economic analysis of cross-breeding programmes in sub-Saharan Africa: A conceptual framework and Kenyan case study - Karugia, Joseph T.; Okeyo Mwai, Ally; Kaitho, R.J.; Wollny, C.B.A.; Drucker, Adam G.; Rege, J.E.O. (International Livestock Research Institute, 2001)
A conceptual framework for evaluating cross-breeding programmes in sub-Saharan Africa is developed based on a Kenyan case study. It depicts livestock production as a system where farm animals, plants, land and water are interlinked in particular ways and are also interlinked with the environment. Depending on the level of intensification and `modernisation', two livestock systems are defined. The first is the traditional livestock production system in which farm animals, plants, land and water are interlinked in a sustainable way with each component complementing the other. The second is a'modern' production system based on crossbreds with varying levels of exotic dairy cattle breeds or pure exotic dairy cattle breeds. Successful cross-breeding not only weakens the interlinkages in the traditional system, but also creates new linkages with external inputs. It is argued that the weakened existing and the newly formed linkages ought to be taken into account when cross-breeding programmes are being evaluated. To accurately evaluate cross-breeding programmes it is, therefore, important to delineate all the outputs and inputs of such a system. In this Report, the outputs and inputs of cattle cross-breeding programmes are defined. Outputs include the marketable products of milk, meat, manure, animal draft power, hides and skins. Inputs include the conventional ones such as research infrastructure, equipment and personnel, extension services, disease control services, exotic germplasm, indigenous germplasm, feeds and marketing infrastructure. Cross-breeding also entails loss of the non-marketed outputs and values of indigenous livestock, such as cultural value, wealth function, existence value, option value and recreation value. An attempt was made to demonstrate the applicability of the developed conceptual framework using the case of cross-breeding Zebu cattle with exotic breeds for dairy improvement in Kenya. Due to time and resource constraints, already existing models that were not specifically developed for the task envisaged in the conceptual framework were applied in the analysis. Some important variables could not be included in the analysis due to data and model limitations. Welfare effects of cross-breeding programmes were estimated using the Kenya Agricultural Sector Model (ASM). The impact of cross-breeding at the farm level was analysed using the Farm Level Income and Policy Simulation Model (FLIPSIM). The two models were developed by the Impact Assessment Group (2000) of Texas A&M University, USA, and applied to evaluate the impact of improved dairy technologies in Kenya in collaboration with the Kenya Agricultural Research Institute (KARI) and the International Livestock Research Institute (ILRI). In this study, these models were used specifically to provide estimates of the economic benefits of crossbreeding indigenous Zebu cattle with exotic dairy breeds. Despite the data and model limitations, the analyses provided useful insights into the benefits and costs of breeding programmes in Kenya.